A rope to tie a lion - International Livestock Research Institute (International Livestock Research Institute, 2012)
This video was planned, filmed and edited by a group of twelve farmers from three kebeles in Fogera woreda in Amhara region of Ethiopia. Gareth Benest from InsightShare, and Beth Cullen and Aberra Adie from ILRI, facilitated the participatory video training which took place between the 12th and 24th February 2012. The aim of the video was to bring local issues to the attention of planners and implementers of rainwater management interventions in Ethiopia. The participatory video training was funded by grant awarded by the CGIAR Challenge Program for Water and Food to investigate and document the effectiveness of participatory video as a 'vertical communication' tool.